Pelot - toivo - luottamus : Näkökulmia Luoteis-Venäjän hiv- ja aids-kysymykseen - Anttila, Marja; Karvonen, Outi; Sinkkonen, Minna; Tuomi, Marja; Vaittinen, Sirje; Vienonen, Anne (Stakes, 2008)
Verkkoversion ISBN 978-951-33-2282-3, ISSN 1795-8105